Legado da educação básica para a alfabetização genética dos cidadãos - Buske, Rodrigo (2019)
Genetic knowledge is increasingly present in everyday life. In this way, this research had as objective to evaluate how the genetic teaching, during the Basic Education in Brazil, is preparing the future citizens to understand, to interact and to make conscious decisions with respect to this knowledge. In order to do so, we elaborated, validated and applied two instruments (questionnaires): one with the specific purpose of evaluating Mendelian inheritance and the other with the objective of evaluating the genetic literacy of citizens who have already completed basic education. The first questionnaire was applied to 114 high school senior students in a public school in Santa Maria - RS, and the second, and main, to 1222 undergraduate students in UFSM. In both instruments, composed of multiple-choice questions, besides the evaluation of genetic knowledge, the students' certainties about their knowledge were also evaluated. The results showed that the genetic literacy provided by basic education in Brazil is still deficient. In general, most citizens do not correctly understand basic concepts and applications of genetics. Yet, several students have demonstrated confidence in their knowledge, ignoring the fact that they are wrong. The media has proven to play an important role in the genetic literacy of students, as well as complementary training in pre-university courses. During the development of the research were also discussed issues about scientific literacy and science teaching, as well as questions about the importance of continuing teacher training. As future perspectives, the main questionnaire will be applied in other universities to obtain more data, thus providing a better picture of the genetic literacy offered by the Basic Education in Brazil.